MONITORING OF AMBIENT AIR QUALITY IN AP VOJVODINA - Vujić, Bogdana; Lazić, Nada; Radovanović-Jovin, Hristina (Economics of Agriculture, 2009)
Since 2002, Provincial Secretariat for Environmental Protection and Sustainable Development is conducting environmental monitoring within the scope of its authority. Monitoring, among the rest, include ambient air quality control in industrial centers and smaller towns, where the possibility of air pollution exists. In the period of 2002-2008., monitoring of ambient air was conducted in 38 cites distributed in 24 settlements. This monitoring comprised 45% of total population of Vojvodina.Besides sistematic control, indicative measurments were conducted. The goal of indicative measurments was to identify pollution in some areas. During 2008, sistem of automatic stations for ambient air quality was established. Sistem has 7 stations located in Subotica, Sombor, Zrenjanin (traffic stations), Kikinda and Novi Sad (industrial stations), Obedska bara and Deliblatska pescara (natural stations).